Pengaruh Transfer Pricing, Profitabilitas, dan Leverage Terhadap Tax Avoidance pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Risma Namira Ivano; Cahyani Nuswandari; Rachmawati Meita Oktaviani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Tax avoidance is a common practice carried out by companies to reduce their tax liabilities using methods that are still within legal limits. The purpose of this study is to analyze the influence of transfer pricing, profitability, and leverage on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange during the period 2019-2023. This study is motivated by the importance of tax revenue from the energy sector and the inconsistency of findings in previous studies. The approach used in this study is quantitative, utilizing secondary data obtained from companies' annual financial reports. The sampling method employed is purposive sampling, resulting in a final sample of 18 companies over a five-year observation period with 60 units of analysis. Analysis was conducted using multiple linear regression after classical assumption tests were satisfied. The results of the study indicate that transfer pricing and profitability significantly influence tax avoidance, whereas leverage does not significantly influence tax avoidance. These findings support agency theory, which explains that managers have incentives to minimize tax burdens to increase company value.